Understanding Primary Teachers’ Perceptions, Self-Efficacy and Integration Practices of Computational Thinking in Finland - Ta, Nguyen (My University, 2025)
The thesis explores how primary school teachers in Finland perceive and integrate computational thinking (CT) into classroom practice, their self-efficacy in relation to CT, as well as the opportunities and challenges they encounter in doing so. As CT has gained increasing attention in national and international curricula, understanding its practical implementation at the primary level is essential for supporting teacher development and fostering 21st-century skills in students. The study was conducted as a cross-sectional survey, in which the survey included multiple-choice items, four 5-point Likert scales, and open-ended questions addressing teachers' self-written definitions of CT, their perceptions of CT and their own integration practices, and perceived opportunities and challenges related to CT integration. 32 teachers answered the survey. Findings suggest that while teachers generally acknowledge the importance of CT, their understanding varies, and integration practices are generally limited. Many teachers reported a lack of confidence, insufficient training, and unclear curriculum guidelines as key challenges. On the other hand, they recognized CT's potential to enhance students’ problem-solving and critical thinking skills, as well as opportunities for creativity. The study highlights the need for quality and sustained professional development opportunities. Supporting teachers with clear guidance and collaborative opportunities is essential for meaningful CT integration in primary education.
Keywords: Computational Thinking (CT), perception, self-efficacy, integration practices, opportunities, challenges, Finland, primary teachers